2019
DOI: 10.3126/ajms.v10i6.25337
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lipid abnormalities and Cardiovascular Risk indices in Type 2 Diabetes Mellitus

Abstract: Background: Incidence of cardiovascular events is increased to two to four times among diabetic patients when compared with non-diabetic. Dyslipidaemia in diabetes is major risk factor for cardiovascular events. Atherogenic indices have been used as major laboratory measures in clinical practice to assess cardiovascular risk. Recent studies, have shown that non-high-density lipoprotein cholesterol and other atherogenic indices is like or better than LDL-C alone in the prediction of CVD incidence and mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…Baral et al reported a higher prevalence of elevated TC/HDL-C ratio (80%), TG/HDL-C ratio (78.4%), and non-HDL-C/ HDL-C ratio (80%) than our study. On the contrary, elevated LDL-C/HDL-C ratio (23.2%) was comparably lower than our study [ 22 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Baral et al reported a higher prevalence of elevated TC/HDL-C ratio (80%), TG/HDL-C ratio (78.4%), and non-HDL-C/ HDL-C ratio (80%) than our study. On the contrary, elevated LDL-C/HDL-C ratio (23.2%) was comparably lower than our study [ 22 ].…”
Section: Discussioncontrasting
confidence: 92%